2022
DOI: 10.3390/ijms23179959
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Biological Properties of Chitosan-Coated Alginate Microparticles Loaded with Porcine Interleukin-1β: A Potential Protein Adjuvant Delivery System

Abstract: We previously developed chicken interleukin-1β (IL-1β) mutants as single-dose adjuvants that induce protective immunity when co-administered with an avian vaccine. However, livestock such as pigs may require a vaccine adjuvant delivery system that provides long-lasting protection to reduce the need for successive booster doses. Therefore, we developed chitosan-coated alginate microparticles as a carrier for bovine serum albumin (BSA) or porcine IL-1β (pIL-1β) and assessed their physical, chemical, and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Zeta-potential measurements revealed that the surface charge of capsules was 15 ± 6 mV. This positive value of zeta potential confirmed that a positively charged chitosan layer was formed successfully above the calcium alginate polymeric structure [ 41 , 42 , 43 , 44 ]. Zeta-potential values above 30 mV are usually sought in order to avoid particle aggregation or flocculation in aqueous dispersion [ 41 , 45 , 46 ] and as reported by Khan et al in their study with resveratrol alginate–chitosan zein nanocapsules; this zeta potential could be increased with higher chitosan to alginate ratios [ 43 ].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Zeta-potential measurements revealed that the surface charge of capsules was 15 ± 6 mV. This positive value of zeta potential confirmed that a positively charged chitosan layer was formed successfully above the calcium alginate polymeric structure [ 41 , 42 , 43 , 44 ]. Zeta-potential values above 30 mV are usually sought in order to avoid particle aggregation or flocculation in aqueous dispersion [ 41 , 45 , 46 ] and as reported by Khan et al in their study with resveratrol alginate–chitosan zein nanocapsules; this zeta potential could be increased with higher chitosan to alginate ratios [ 43 ].…”
Section: Resultsmentioning
confidence: 62%
“…Many of the factors that affect particle size (i.e., alginate concentration, voltage, needle size, encapsulation flowrate and hardening solution’s surface tension, viscosity and stirring rate [ 26 , 49 , 50 ]) were previously optimized following the same methodology used in our research group [ 24 ]. Hence, the lack of complete sphericity could be attributed to the freeze-drying step, which affects negatively the sphericity [ 42 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carriers commonly used were alginate, PEO and NOSC, all of which are particularly used for the formulation of oral delivery drugs since they are all safe and present high biocompatibility. Alginate was used to encapsulate α-calcitonin gene-related peptide (α-CGRP) [97] and BSA/porcine interleukin-1β (pIL-1β) [100], both by blend electrospraying and resulting in particles with widely differing sizes, ranging from 194.23 ± 10.08 to 20 µm, respectively. PEO is a synthetic semicrystalline polymer mostly used for electrospinning due to its rheological characteristics, and thus only one work used it for electrospraying the enzyme alkaline phosphatase [95,104].…”
Section: Formulation Of the Feed Streammentioning
confidence: 99%
“…Attributes such as controlled, sustained and specific release to cells and/or tissues can be conferred to microparticles. It is also possible to administer poorly soluble drugs [ 12 ], to overcome epithelial and endothelial barriers [ 13 ], co-administer two or more bioactive agents for combined therapy [ 14 ], select adjuvants for improving the immune response of vaccines [ 15 ], and increase effectiveness, safety and bioavailability of therapeutic agents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%